2016
DOI: 10.1556/018.67.2016.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid induced cysteine protease activity during programmed cell death in tomato plants

Abstract: The hypersensitive response (HR), a type of programmed cell death (PCD) during biotic stress is mediated by salicylic acid (SA). The aim of this work was to reveal the role of proteolysis and cysteine proteases in the execution of PCD in response of SA. Tomato plants were treated with sublethal (0.1 mM) and lethal (1 mM) SA concentrations through the root system. Treatment with 1 mM SA increased the electrolyte leakage and proteolytic activity and reduced the total protein content of roots after 6 h, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…In this article, comparative biochemical and molecular analyses of HXKs were carried out in time course experiments after sublethal (0.1 mM) and cell death-inducing (1 mM) SA treatments in order to reveal their putative role in the initiation of cell death in tomato leaves. The appearance of cell death symptoms in tissues of tomato plants exposed to these SA concentrations have already been studied in our group (Kovács et al 2016;Poór et al 2013). It was found that the first markers of PCD appeared 24 h after SA treatment, so this point seemed to be suitable to compare the differences between the effects of the two SA concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, comparative biochemical and molecular analyses of HXKs were carried out in time course experiments after sublethal (0.1 mM) and cell death-inducing (1 mM) SA treatments in order to reveal their putative role in the initiation of cell death in tomato leaves. The appearance of cell death symptoms in tissues of tomato plants exposed to these SA concentrations have already been studied in our group (Kovács et al 2016;Poór et al 2013). It was found that the first markers of PCD appeared 24 h after SA treatment, so this point seemed to be suitable to compare the differences between the effects of the two SA concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, the execution of cell death is mediated by the induction of cysteine proteases, some of them showing caspase-like activities. Caspase-like activity seems to be activated by K + deficiency in plant cells (Demidchik et al 2010), which is in good correlation with the induction of cysteine protease activity in salt-stressed plants (Kovács et al 2012). …”
Section: No-and Salt-induced Programmed Cell Deathmentioning
confidence: 82%
“…Loss of mitochondrial integrity and cyt c release from mitochondria takes place before cell death execution [45,92]. This cyt c release can activate various cysteine proteases in the cytosol whose activities and the expression of its coding sequences were elevated by SA [97,101,[113][114][115][116]. Cell death in plant organs is preceded by various cytological and biochemical features ( Figure 1): specific morphological changes, rupture of vacuole membrane tonoplast, activation of proteases and nucleases, chromatin aggregation and DNA fragmentation [42][43][44][45][46]117], which hallmarks of PCD were also detected upon SA treatments [97,101].…”
Section: Sa-induced Lethal Mitochondrial Oxidative Stress and Mitochomentioning
confidence: 99%